Ten thousand stitches - Atwater, Olivia (Atwater, Olivia. Regency faerie tales, 2022)
Risking her immortal soul to win Mr. Benedict Ashbrooke's heart, housemaid Effie has 100 days-- and 10,000 stitches-- to make Mr. Ashbrooke fall in love and propose, she finds her greatest obstacle might be the man with whom she made a devil's bargain whose overwhelmingly good intentions stand in her way.